Guidelines for thermography in architecture and civil engineering theory, application area, practical implementation - Richter, Torsten, 1972- (Birkhäuser, 2021)
What does it take to obtain significant measurement results in thermographic examinations? These guidelines convey in condensed form the authors' many years of experience in detecting thermal engineering defects and structural damage such as thermal bridges, air leaks or moisture penetration damage with a non-destructive and easily applicable method of measurement and investigation. As well as providing an introduction to the physical fundamentals of thermography, the book offers an up-to-date overview of the technology, structure, standards and selection criteria of common thermographic systems. Using selected examples, it shows the many possibilities and areas of application of infrared thermography as well as the limits of its use.